Unusual Case of Massive Obscure Gastrointestinal Bleeding: Ectopic Varices in Jejunum Caused by Arteriovenous Malformation - Hasan Maulahela; Kaka Renaldi; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2018)
Small bowel ectopic varices is a rare etiology for obscure gastrointestinal bleeding. Ectopic varices in the absence of portal hypertension can be caused by congenital or familial conditions (e.g. malformation of vessel). Bleeding caused by ectopic varices can be massive and life threatening. Single Balloon Enteroscopy (SBE) is one of diagnostic modalities for obscure gastrointestinal bleeding. We report one case of obscure overt gastrointestinal bleeding with sub-acute onset. Previous esophagogastroduodenoscopy and colonoscopy cannot found the source of bleeding. On the enteroscopy we found varices at proximal jejunum with active bleeding during procedure. We applied hemostatic powder to stop the bleeding and proceed to surgery. Surgery was performed by enteroscopy guide. The jejunum section with varices was resected and the pathology confirmed the malformation of arteriovenous. Currently there is no available guideline or randomized study for the treatment of ectopic varices. Treatment options include ligation, sclerotherapy, surgery and interventional radiology. In this patient we choose surgery because of massive gastrointestinal bleeding.